2010
DOI: 10.1021/jp105097z
|View full text |Cite
|
Sign up to set email alerts
|

Density Functional Calculations and IR Reflection Absorption Spectroscopy on the Interaction of SO2 with Oxide-Supported Pd Nanoparticles

Abstract: A systematic study on the interaction of sulfur dioxide (SO2) on BaO-supported Pd nanoparticles has been carried out using suitable models and state-of-the-art density functional (DF) calculations. Detailed information concerning the structure and energetics of the different conformations of adsorbed SO2 is provided as a function of coverage together with calculated infrared reflection absorption spectroscopy (IRAS) spectra. SO2 may adsorb on Pd(111) in several conformations, some active, η2-SbOa and η1-Sb, an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 19 publications
(38 citation statements)
references
References 77 publications
5
33
0
Order By: Relevance
“…24 More details of the model, the slab representing the surface, as well as of the isolated SO x (x = 1-4) species, and the S and O atoms can be found elsewhere. 8,36 To allow for a comparison with previous studies 8,25,[36][37][38][39] calculations have been carried out using the Perdew-Wang 40 (PW91) exchange-correlation functional.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…24 More details of the model, the slab representing the surface, as well as of the isolated SO x (x = 1-4) species, and the S and O atoms can be found elsewhere. 8,36 To allow for a comparison with previous studies 8,25,[36][37][38][39] calculations have been carried out using the Perdew-Wang 40 (PW91) exchange-correlation functional.…”
Section: Methodsmentioning
confidence: 99%
“…2,45 Finally, the notation of different adsorption sites used throughout the study follows that suggested earlier. 8,25,[36][37][38][39] In short, for any given species and adsorption mode, η x and μ y keys denote that x atoms of the molecule (η x ) are bound to y surface Pd atoms (μ y ).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Pt NPs are typicallyu sed as the active phase in NSR, [16,17] with very high activities and essentially ac ompleteN Oc onversion. However,t hey display certain drawbacks, including i) al ow selectivity towards N 2 species, ii)susceptibility towards sulfur poisoning owing to the competitive adsorption of SO x speciesa nd/or their perturbation effecto nt he Pt electronic structure, [17][18][19] and iii)the high cost of the preciousP t. Quite interestingly,t he Cu@Pt NPs maintain the high reactivity of Pt NPs with am uch better N 2 selectivity,u pt o9 3%,a nd remain stable under the catalytic workingt emperature of 360 8C. In contrast, Pt@CuN Ps showed very little NO conversion,apriori,o wing to the Cu-rich shell structure, and the N 2 selectivity wasf ound to drop over time until meeting that of the CuPt alloy.…”
Section: Introductionmentioning
confidence: 99%
“…From the theoretical perspective, density functional theory (DFT) based calculations have been carried out to investigate the poisoning mechanism of SOx 4) on Pd catalysts [15 18]. Using infrared absorption spectroscopy (IRRAS), X-ray photoelectron spectroscopy (XPS), and DFT calculations, Luckas et al reported the adsorption and reactivity of SO2 on Pd/BaO, Pd(111) [15], and oxygen pre-covered Pd(100) surfaces [16]. The energetically preferred adsorption orientation of SO2 on Pd(100) was the molecular plane perpendicular to the Pd surfaces, and the oxidation of SO2 led to SO3…”
Section: Introductionmentioning
confidence: 99%